Successful vaginal delivery of spontaneously conceived twins in each horn of a bicornuate uterus with previous caesarean: a case report - Mazhari, Farhat; De, Arpita; Tripathi, Reva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Mullerian duct fusion anomalies resulting in uterine malformations have prevalence of 3-4%. Among this, bicornuate uterus has a rare incidence of 0.4%. Uterine malformations pose significant threat in terms of obstetric outcomes. We report an extremely rare case of spontaneous conception of twin pregnancy with the fetus occupying each horn of a bicornuate uterus (bicornis unicollis), in a woman with a history of previous caesarean section. She was booked at our hospital and the pregnancy remained uneventful. At 35 weeks she went into spontaneous labour and delivered vaginally without any maternal-fetal complications. The case is unique and the management is worth discussing as till date no protocols or guidelines have been proposed for the mode of delivery of bicornuate uterus with twins with previous cesarean. Only 12 cases of twins with bicornuate uterus have been reported till date. This is the first case in literature in which a successful VBAC has been conducted in a woman with bicornuate uterus with twins with previous caesarean.